Konsep Konstitusi Beserta Lembaga Mahkamah Konstitusi di Indonesia - Rahmah, Anisa; Kristanto, Budi; Jamaluddin, Jamaluddin (EduInovasi: Journal of Basic Educational Studies, 2024)
Based on the developments that have occurred in Indonesia since August 18, 1945, this research explains how the idea of the constitution was born. The author's goal is to delve into various ideas and laws related to the Indonesian constitution. This research uses normative juridical methodology; qualitative descriptive analysis and secondary data collection are the backbone of the research. The research results show that the Indonesian Constitution has undergone four changes, namely from the 1945 Constitution to the RIS Constitution, the 1950 Constitution, and back to the 1945 Constitution. These changes have been influenced by internal and external factors, as well as different political and legal situations in Indonesia. Therefore, Indonesia's state system continues to evolve. In conclusion, in Indonesia, the constitution continues to undergo revisions. Several factors contribute to the evolution of the Indonesian constitution. One of them is the hasty and imperfect drafting of the BPUPKI document. Another example is the pressure from the Netherlands, which led to the amendment of the 1945 Constitution, changing the legal politics of the state and the constitutional framework of the Republic of Indonesia.